RETORIKA DAN TEKNIK DEBAT POLITIK - Marzuki Marzuki; Alwi Hadad; Dinda Ratulangi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Political debates are one of the main instruments of democracy, serving as a platform for candidates to present their ideas and for the public to assess the credibility and capabilities of potential leaders. Rhetoric plays a key role in political debates, with the three main elements of Aristotle’s theory—ethos, pathos, and logos—forming the foundation of effective political communication. Ethos emphasizes the speaker's credibility, pathos appeals to the audience’s emotions, and logos relates to arguments based on logic and facts. However, in practice, many candidates use manipulative rhetorical techniques such as logical fallacies, including straw man argument, false dilemma, and ad hominem, which can mislead public opinion. This study employs a qualitative descriptive approach with content analysis of the 2024 presidential election debates to identify the use of rhetorical techniques in political debates. The findings reveal that effective rhetoric can enhance a candidate’s electability and shape public perception, while manipulative rhetoric can create polarization in society. Therefore, strong political literacy is necessary for the public to analyze debates objectively and avoid being influenced by manipulative techniques.